Boosting the Enantioselectivity of Conjugate Borylation of α, β‐Disubstituted Cyclobutenones with Monooxides of Chiral C2‐Symmetric Bis(phosphine) Ligands. Issue 62 (1st September 2022) - Cui, Ming; Zhao, Zhi‐Yuan; Oestreich, Martin
Abstract: Chiral bis(phosphine) monooxides (BPMOs) derived from C 2 ‐symmetric bis(phosphines) have been found to induce superior levels of enantioselection in copper‐catalyzed conjugate borylation of α, β‐disubstituted cyclobutenones. More precisely, enantiomeric excesses as well as chemical yields are exceedingly high with ( R, R )‐Bozphos as the chiral ligand while these values are low with parent ( R, R )‐Me‐Duphos. A similar yet less pronounced effect was seen in the corresponding 1, 6‐addition to para ‐quinone methides. Abstract : A chiral bis(phosphine) monooxide (BPMO) derived from a C 2 ‐symmetric bis(phosphine) ligand does magic to the copper‐catalyzed conjugate borylation of α, β‐disubstituted cyclobutenones. Yields and levels of stereoselection, especially enantioselectivity, are exceedingly high (see scheme).